A Novel Prognostic Signature Associated with Immunotherapeutic Response for Hepatocellular Carcinoma - Jin, Xinmin; Wang, Jinhuan (Frontiers in Surgery, 2022)
Background: Although accumulating literature has validated that necroptosis plays a prominent role in the tumorigenesis and progression of various malignant cancer, its mechanism in hepatocellular carcinoma (HCC) is poorly understood. Therefore, in the present study, we want to study the impact of necroptosis related genes on the prognosis, microenvironment infiltrated immunocytes, and the effects of immunotherapy in patients with HCC. Methods: The necroptosis related genes were obtained by reviewing the available published literature, we then evaluated the effects of the prognostic genes to on the relative abundance of microenvironment infiltrated immunocytes. After construction of the Risk Score Signature, we evaluated the prognostic value and the effects on immune cells infiltrating the tumor microenvironment (TME). Combining the available data on immunotherapy, we also investigated the impact on anti-PD-L1-based immunotherapy. Results: A comprehensive study of the published literature confirmed the 22 genes to be related to necroptosis. Among them, 10 genes were related to the prognosis of the HCC cohort in The Cancer Genome Atlas (TCGA), and had a multifaceted influence on TME. We obtained the Risk Score Signature by Lasso regression. Furthermore, we also corroborated the correlation between the Risk Score Signature and tumor-infiltrated immune cells in the TME. Next, in the study of the correlation between the Signature and immunotherapy, we found the Signature was significantly correlated with the reactivity of anti-PD-L1 immunotherapy. We also confirmed that the Risk Score Signature is a reliable and efficient independent prognostic marker of HCC. Conclusion: We established a novel and effective prognostic model for patients with HCC, which is markedly related to the TME and immune infiltration in HCC and can also predict immunotherapeutic response and prognosis.